2023
DOI: 10.2196/42767
|View full text |Cite
|
Sign up to set email alerts
|

Integrating User Preferences for Asthma Tools and Clinical Guidelines Into Primary Care Electronic Medical Records: Mixed Methods Study

Abstract: Background Asthma is a chronic respiratory disease that poses a substantial burden on individuals and the health care system. Despite published national guidelines for the diagnosis and management of asthma, considerable care gaps exist. Suboptimal adherence to asthma diagnosis and management guidelines contributes to poor patient outcomes. The integration of electronic tools (eTools) into electronic medical records (EMRs) represents a knowledge translation opportunity to support best practices. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In addition, in EMRs, there is no requirement for confirming asthma diagnosis through objective measures such as spirometry or a methacholine challenge test. EMRs should incorporate data elements such as those proposed by the Pan-Canadian Respiratory Standards Initiative for Electronic Health Records (PRESTINE) so that providers are able to document whether asthma is suspected or confirmed, and if confirmed by what method [7,20]. Data elements that capture if asthma has been confirmed would enable case definition search strategies to differentiate between suspected and confirmed asthma [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in EMRs, there is no requirement for confirming asthma diagnosis through objective measures such as spirometry or a methacholine challenge test. EMRs should incorporate data elements such as those proposed by the Pan-Canadian Respiratory Standards Initiative for Electronic Health Records (PRESTINE) so that providers are able to document whether asthma is suspected or confirmed, and if confirmed by what method [7,20]. Data elements that capture if asthma has been confirmed would enable case definition search strategies to differentiate between suspected and confirmed asthma [19].…”
Section: Discussionmentioning
confidence: 99%
“…A rule-based algorithm was developed to categorise confirmed and suspected asthma patients in an observational study, and support asthma educators to adhere to the best practice guidelines in recognising and managing uncontrolled severe asthma. The authors showed that a machine learning algorithm can be used to classify asthma patients in a future clinician decision support system, improving asthma underdiagnosis/misdiagnosis, and operating as a surveillance system [89][90][91][92].…”
Section: Electronic Health Recordmentioning
confidence: 99%